Management control systems in small medium hotels and their effect on performance - Mohamed, Rapiah; Muhammad Jamil, Che Zuriana (American Scientific Publishers, 2015)
Management control systems (MCS) are an important concept in management accounting.However, prior literature focuses on the MCS in large corporations, while very little research has been conducted on small medium enterprises (SME). The objective of this paper is to examine the relationship of MCS based on Simons’ levers of control framework and the performance of SME hotel.The data were collected from hotel managers using a mail survey.The findings demonstrate that MCS is important to enhance hotel performance, but that only diagnostic control has a significant relationship with hotel performance.The results imply that traditional control systems contribute to firm performance, but, that, in future, SME hotel managers could also consider other types of control system i.e., belief, boundary and interactive to help them to enhance performance.